Predictive Value of Inflammation Markers for Frailty in Older Patients with CVD - Hu S; Lai X; Shi Y; Chai H; Guo Z; Liu D; Cui C (Clinical Interventions in Aging)
Suiyuan Hu,1,* Xuan Lai,1,* Yanyan Shi,2,* Haodi Chai,3,4 Zhijun Guo,5 Dongyang Liu,3,4,6 Cheng Cui3,4 1Geriatrics Department, Peking University Third Hospital, Beijing, People’s Republic of China; 2Research Center of Clinical Epidemiology, Peking University Third Hospital, Beijing, People’s Republic of China; 3Drug Clinical Trial Center, Peking University Third Hospital, Beijing, People’s Republic of China; 4Center of Clinical Medical Research, Institute of Medical Innovation and Research, Peking University Third Hospital, Beijing, People’s Republic of China; 5Department of Gastroenterology, Peking University Third Hospital, Beijing, People’s Republic of China; 6State Key Laboratory of Vascular Homeostasis and Remodeling, Drug Clinical Trial Center, Peking University Third Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Cheng Cui; Dongyang Liu, Email cuicheng1226@163.com; liudongyang@vip.sina.comBackground: Chronic inflammation plays a pivotal role in the development of frailty in patients with cardiovascular diseases (CVD). Systemic inflammatory response index (SIRI) has been shown to reflect the overall inflammatory status. This study aimed to investigate the relationship between SIRI and frailty in older patients with CVD, and to develop a nomogram for predicting the risk of frailty in this population.Methods: A total of 234 older patients with CVD were included. Inflammation markers were derived from routine blood tests, and frailty status was assessed using the FRAIL scale. Clinical and laboratory characteristics were compared between patients with or without frailty. Multivariate logistic regression was employed to identify significant variables for inclusion in the nomogram. The performance of the nomogram, including its discrimination and calibration, was rigorously evaluated.Results: A total of 98 cases were assigned to the frailty group and 136 to the non-frailty group. Patients in the non-frailty group were generally younger, more likely to have normal kidney function, and better blood pressure control. Frail patients exhibited a higher degree of systemic inflammation compared to non-frail patients (P < 0.05). Age, LDL-C and SIRI were identified as three independent risk factors with significant potential for predicting frailty in CVD patients. Therefore, we constructed a clinical nomogram model for frailty based on age, LDL-C and SIRI. The nomogram for frailty had considerable discriminative and calibrating abilities.Conclusion: In summary, our study demonstrated a significant association between elevated levels of inflammation markers, particularly SIRI, and an increased risk of frailty. Furthermore, by integrating age, LDL-C and SIRI, we established a nomogram to predict the risk of frailty in older patients with CVD.Keywords: inflammation markers, systemic inflammatory response index, frailty, cardiovascular diseases, nomogram